Robust Resolution of Velocity Ambiguity for Multi-Frequency Pulse-to-Pulse Coherent Doppler Sonars - CHI CHENG (Institute of Electrical and Electronics Engineers (IEEE), 2019)
10.1109/JOE.2019.2925919